Cryptography with shrinking generators : fundamentals and applications of keystream sequence generators based on irregular decimation /: fundamentals and applications of keystream sequence generators based on irregular decimation. (2019) - Díaz Cardell, Sara; Fúster Sabater, Amparo
No abstract available